Security, identity, and interests : a sociology of international relations - McSweeney, Bill. (Cambridge, U.K. ; New York : Cambridge University Press, 1999)
In this book, Bill McSweeney discusses the inadequacy of the scientific approach to security and criticizes the most recent attempts to surmount it. Drawing on contemporary trends in sociology, he develops a theory of the international order within which the idea of security takes on a broader range of meaning.
The meaning of security -- pt. 1. Objectivist approaches to international security. Early stages of development. Broadening the concept of security. Identity versus the state -- pt. II. Theorizing security: the turn to sociology. A conceptual discussion. The social constructionist approach. The limits of identity theory. Agency and structure in social theory. Seeing a different world: a reflexive sociology of security -- pt. III. Practising security. Doing security by stealth. Conclusion: Security and moral choice.
Includes bibliographical references (pages 220-237) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: International relations -- Sociological aspects; Relations internationales -- Aspect sociologique; POLITICAL SCIENCE -- Globalization; International relations -- Sociological aspects; Internationale Politik; Sicherheitspolitik; Soziologie; Internationale betrekkingen; Sociologische aspecten; Relações internacionais (aspectos sociais); Relations internationales -- Aspect sociologique; Samfundsvidenskab -- Politologi; Electronic books; Electronic books